Head and Neck Lymphedema: Treatment Response to Single and Multiple Sessions of Advanced Pneumatic Compression Therapy. (April 2019) - Gutierrez, Carolina; Karni, Ron J.; Naqvi, Syed; Aldrich, Melissa B.; Zhu, Banghe; Morrow, J. Rodney; Sevick-Muraca, Eva M.; Rasmussen, John C.
Ten head and neck cancer survivors diagnosed with head and neck lymphedema (HNL) were imaged using near-infrared fluorescence lymphatic imaging (NIRFLI) prior to and immediately after an initial advance pneumatic compression device treatment and again after 2 weeks of daily at-home use. Images assessed the impact of pneumatic compression therapy on lymphatic drainage. Facial composite measurement scores assessed reduction/increase in external swelling, and survey results were obtained. After a single pneumatic compression treatment, NIRFLI showed enhanced lymphatic uptake and drainage in all subjects. After 2 weeks of daily treatment, areas of dermal backflow disappeared or were reduced in 6 of 8 subjects presenting with backflow. In general, reductions in facial composite measurement scores tracked with reductions in backflow and subject-reported improvements; however, studies are needed to determine whether longer treatment durations can be impactful and whether advanced pneumatic compression can be used to ameliorate backflow characteristic of HNL.